Chapter A Scientometric Study on Graphene and Related Graphene- Based Materials in Medicine - Barboni, Barbara (InTechOpen, 2018)
Here we carried out a scientometric analysis of scientific literature published referred to the use of graphene and graphene-based materials. We found that in the last 15 years, more than 1200 issues have been produced, with an H-index of 67 cited 2647 times. The countries that have a larger production, in terms of number of issues published, are China, the United States, South Korea, India, and Iran, and the most relevant subject categories in which they are indexed are materials science, chemistry, science and technology, physics, and engineering, while the biological and medical specialties seem to be actually not deeply involved.